Wellness Aging Model Related to Inactivity, Illness, and Injury (WAMI-3): A Tool to Encourage Prevention in Practice. Issue 4 (13th October 2022) - Billek-Sawhney, Barbara; Criss, Michelle G.; Galantino, Mary Lou; Sawhney, Rajiv
Abstract : It is a steep challenge to fully implement the wide range of evidence that supports rehabilitation interventions for the prevention of chronic disease. Proactive physical activity (PA) promotion can lead to increased PA levels to improve and maintain physical function. Higher levels of PA throughout the lifespan lead to better overall population health, wellness, aging, disease prevention, and chronic condition management. This article introduces the Wellness Aging Model related to Inactivity, Illness, and Injury (WAMI-3) as a simple visual tool to educate patients on the importance of PA and exercise for primary, secondary, and tertiary prevention. As a clinical construct, the WAMI-3 can be applied to all body systems affected by aging, inactivity, illness, and/or injury and exemplifies the concept of Exercise is Medicine ®. The WAMI-3 framework is intended for easy integration into clinical practice; a clinician-friendly resource, based on health promotion, is provided to serve as a catalyst for enhancing the patient interview and education on the importance of PA and exercise. Video Abstract available: For more insight from the authors, see Supplemental Digital Content 1 (available at: http://links.lww.com/JGPT/A115 )